MUZAKKI COMPLIANCE IN PAYING AGRICULTURAL ZAKAT - Fatimah, Siti; Satibi, Ibi (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
This study examines the compliance level of muzakki in paying agricultural zakat in Indonesia, a religious obligation with significant potential to support wealth redistribution and poverty alleviation. Although Indonesia is recognized as the country with the largest Muslim population globally and substantial agricultural zakat potential, the actual collection of this zakat remains far from optimal. The low compliance rate among muzakki is attributed to various factors, such as a lack of understanding of zakat laws, weak regulatory oversight, and socio-economic challenges faced by farmers. This study aims to contribute to the development of more effective agricultural zakat management policies to support community empowerment and reduce socio-economic disparities. This research employs a qualitative method with a literature review approach to analyze the factors influencing muzakki compliance, including religiosity, financial capability, knowledge, and the transparency of zakat management institutions. The findings suggest that improving education, optimizing zakat institution governance, and providing flexible payment mechanisms can enhance muzakki participation.